BRANCHED MACROCYCLIC 4-(PYRAZOL-5-YL)-INDOLE DERIVATIVES AS INHIBITORS OF MCL-1 - ROMBOUTS, Frederik Jan Rita; VELTER, Adriana-Ingrid; FERRER CABRERA, Sofia; BUIJNSTERS, Petrus Jacobus Johannes Antonius (2024)
The present invention relates to pharmaceutical agents of formula (I) useful for therapy and/or prophylaxis in a subject, pharmaceutical composition comprising such compounds, and their use as MCL-1 inhibitors, useful for treating diseases such as cancer.